PEDAGOGICAL BASES OF PEDAGOGY OF HAPPINESS (Education in the 21st Century, 2023)
Pedagogy of happiness is regarded as a non-classical pedagogy of the 21st century, which determines search path of the pedagogical knowledge system evolution as a component of the ongoing educational reforms. Pedagogy of happiness is a creative pedagogy in itself. It is a pedagogical system, where the culture of joy and happiness as a culture of creativity and health stands for integrating all pedagogical systems. Happiness is one of the most important components of human life, which reveals the level of life fulfilment and is an important characteristic feature of human life. Happiness is health, joy, love, freedom, creativity, good family, good job, as well as a harmony with oneself and the world.Felixology is a new branch in the educational process, which presents the problem of the happiness as a pedagogical problem. Felixological motive is found in the personal perfection.    Nowadays the emphasis on the child's happiness is the most demanded one, as education has a leading role in the socialization process, and strive for happiness is the main driving force in the human society.  The ability to be happy is not inheritable quality; it cannot be inherited and cannot be given to the child by parents or teachers. It develops during the whole life: in family, kindergarten, school and other social institutions.The article analyses the connection between human health and happiness. It is suggested that the issue of the protection of children's health and the healthy lifestyle is the subject of pedagogical valeology, which is the core of a person's comprehensive developmental system. The article concludes that the purpose of today's school should be to educate and bring up not only intelligent but also a healthy and happy generation - the demand of the 21st century.